APPROACHES REGARDING THE SUSTAINABILITY AND ENVIRONMENTAL PROTECTION IN THE PHARMACEUTICAL INDUSTRY - Daniela CÎRŢÎNĂ (Fiabilitate şi Durabilitate)
Sustainability and environmental protection are currently priorities of the pharmaceutical industry, a field in which more and more companies are interested in developing and implementing innovative technologies, finding sustainable solutions in the production of medicines whereby the chemical processes for producing pharmaceutical preparations are subsidiary to green chemistry. In this context, major drug manufacturers are promoting new synthesis processes involving biocatalysis reactions, the use of as few solvents as possible and a considerable reduction in the quantities and types of production waste, thus succeeding in applying the sustainability challenge on a global scale.